Solve the following system of linear equations using (a) substitution and (b) determinants. \[ \begin{array}{r}3 x+5 y-13 \\ x-2 y=0.75\end{array} \]
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
Let’s solve the system of equations step by step using substitution first. ### (a) Substitution Method We have the system of equations: 1. \( 3x + 5y = 13 \) 2. \( x - 2y = 0.75 \) **Step 1: Solve one equation for one variable.** From the second equation, solve for \( x \): \[ x = 2y + 0.75 \] **Step 2: Substitute this expression for \( x \) into the first equation.** Substitute \( x \) into the first equation: \[ 3(2y + 0.75) + 5y = 13 \] **Step 3: Simplify and solve for \( y \).** \[ 6y + 2.25 + 5y = 13 \] \[ 11y + 2.25 = 13 \] \[ 11y = 13 - 2.25 \] \[ 11y = 10.75 \] \[ y = \frac{10.75}{11} \approx 0.976 \] **Step 4: Substitute back to find \( x \).** Now substitute \( y \) back to find \( x \): \[ x = 2(0.976) + 0.75 \approx 1.952 + 0.75 = 2.702 \] So, the solution is approximately \( x \approx 2.702 \) and \( y \approx 0.976 \). ### (b) Determinants Method (Cramer's Rule) Using Cramer’s rule, we need the coefficients of the system: \[ \begin{align*} 3x + 5y &= 13 \\ x - 2y &= 0.75 \end{align*} \] **Step 1: Determine the coefficient matrix and constant matrix.** \[ A = \begin{bmatrix} 3 & 5 \\ 1 & -2 \end{bmatrix}, \quad B = \begin{bmatrix} 13 \\ 0.75 \end{bmatrix} \] **Step 2: Calculate the determinant of the coefficient matrix.** \[ D = \text{det}(A) = 3 \cdot (-2) - 5 \cdot 1 = -6 - 5 = -11 \] **Step 3: Calculate determinants for \( x \) and \( y \).** \[ D_x = \text{det}\begin{bmatrix} 13 & 5 \\ 0.75 & -2 \end{bmatrix} = 13 \cdot (-2) - 5 \cdot 0.75 = -26 - 3.75 = -29.75 \] \[ D_y = \text{det}\begin{bmatrix} 3 & 13 \\ 1 & 0.75 \end{bmatrix} = 3 \cdot 0.75 - 13 \cdot 1 = 2.25 - 13 = -10.75 \] **Step 4: Solve for \( x \) and \( y \).** \[ x = \frac{D_x}{D} = \frac{-29.75}{-11} \approx 2.704 \] \[ y = \frac{D_y}{D} = \frac{-10.75}{-11} \approx 0.976 \] Thus, the solution using both methods results in \( x \approx 2.704 \) and \( y \approx 0.976 \).